Challenges to The Government’s Efforts to Fight HIV/AIDS: A Literature Review - Sartika Sartika (Jurnal EduHealth, 2023)
The government's efforts to deal with HIV/AIDS are essential and vital as a manifestation of their responsibility to improve the quality of healthcare system, as mandated by the law. This is urgent because HIV/AIDS problems are an ongoing issue that is remain unsolved while it is being exacerbated by the emergence of the COVID-19 pandemic, which has made the efforts to cope with HIV/AIDS became more difficult to do. Therefore, the government is working in various efforts to overcome HIV/AIDS in Indonesia. This study attempted to examine the extent of the government's role in addressing HIV/AIDS. Literature review is used as the method to carry out this study by collecting and identifying a number of scientific publications on related topics. The results of the analysis indicate that the government has attempted to play a role in dealing with HIV/AIDS, but majority of the studies considered that the government's role had not been effective. It is important to strengthen, applying new strategies, and the involvement of various stakeholders for HIV/AIDS prevention efforts to be effective.